Squeezed vacuum states from a whispering gallery mode resonator - Otterpohl, Alexander; Sedlmeir, Florian; Vogl, Ulrich; Dirmeier, Thomas; Shafiee, Golnoush; Schunk, Gerhard; Strekalov, Dmitry V.; Schwefel, Harald; Gehring, Tobias; Andersen, Ulrik Lund; Leuchs, Gerd; Marquardt, Christoph (Optica, 2019)
Squeezed vacuum states enable optical measurements below the quantum limit and hence are a valuable resource for applications in quantum metrology and also quantum communication. However, most available sources require high pump powers in the milliwatt range and large setups that hinder real-world applications. Furthermore, degenerate operation of such systems presents a challenge. Here, we use a compact crystalline whispering gallery mode resonator made of lithium niobate as a degenerate parametric oscillator. We demonstrate about 1.4 dB noise reduction below the shot-noise level for only 300 mu W of pump power in degenerate single-mode operation. Furthermore, we report a record pump threshold as low as 1.35 mu W. Our results show that the whispering gallery-based approach presents a promising platform for a compact and efficient source for nonclassical light. (c) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-12-06